Trophodynamics of carnivorous zooplankton in the region of the subtropical convergence within the Indian sector of the Southern Ocean, with particular emphasis on chaetognaths - Sterley, Jessica Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
Trophodynamics of carnivorous zooplankton in the region of the Subtropical Convergence (STC) in the Indian sector of the Southern Ocean was investigated during austral autumn (April 2007) as part of the first cruise of the Southern Ocean Ecosystem Variability Study. Within the region of the study, the STC was well defined by the 14Â°C surface isotherm which separated the Agulhas Return Current and Subtropical water in the north from Sub-Antarctic waters to the south. Total average abundance (3.89 Â± 5.46ind 100m-3) and biomass (0.14 Â± 0.27mg Dwt 100m-3) of carnivorous zooplankton south of the front were significantly higher than the total average abundance (1.33 Â± 1.81ind 100m-3) and biomass (0.03 Â± 0.05mg Dwt 100m-3) north of the front (p<0.001). There were no significant correlations between the selected physico-chemical (temperature and salinity) and the biological (mesozooplankton abundance and biomass) variables and the total abundance and biomass of the carnivorous zooplankton during the investigation (p>0.05 in all cases). There was no evidence of enhanced biomass and abundance values at stations occupied in the immediate vicinity of the front. Total average carnivorous zooplankton abundance was dominated by chaetognaths (Eukrohnia hamata Möbius 1875, Sagitta gazellae Ritler-ZÃ¡hony 1909 and S. zetesios Fowler 1905) and euphausiids (Nematoscelis megalops Sars 1883, Euphausia longirostris Hansen 1908 and E. spinifera Sars 1883), which contributed up to 86.58 Â± 32.91% of the total counts. The total average biomass was dominated by euphausiids and amphipods (Themisto gaudichaudii Guérin-Méneville 1825, Phronima sedentaria ForsskÃ¥l 1775 and Vibilia armata Bovallius 1887) which contributed up to 71.45 Â± 34.85% of the total counts. In general the populations of both the euphausiids and amphipods were dominated by females while the chaetognaths were dominated by juveniles. Numerical analysis identified two major zooplankton groupings within the survey area which did not coincide with the water masses within the survey area. The SIMPER procedure of the PRIMER package indicated differences between the groups were mainly attributed to changes in the abundance of the numerically dominant species rather than the presence or absence of individual species. The absence of any significant spatial patterns in the distribution of the carnivorous zooplankton suggests that the STC did not act as a biogeographical barrier during the present study. The mean feeding rates of the chaetognaths E. hamata, S. gazellae and S. zetesios were 1.82 Â± 0.85prey d-1, 3.63 Â± 2.08prey d-1 and 2.18 Â± 0.59prey d-1, respectively. These rates correspond to a combined predation impact equivalent to <5% of the mesozooplankton standing stock or <10% of the mesozooplankton secondary production. Mesozooplankton, comprising mainly copepods was the dominant prey in the guts of the three chaetognath species. Total predation impact of the euphausiids, chaetognaths and amphipods, estimated using published daily ration data, on the mesozooplankton standing stock and secondary production ranged from 0.01% to 1.53% and from 0.03% to 30.54%, respectively. Among the carnivorous zooplankton, chaetognaths were generally identified as the dominant predators of mesozooplankton. Low predation impact of selected carnivorous zooplankton suggested that these organisms contributed little to the vertical carbon flux within the region of investigation during the study.
Keywords: Zooplankton -- Antarctic Ocean; Chaetognatha; Euphausiacea; Amphipoda; Predation (Biology)